2019
DOI: 10.1186/s41043-019-0189-x
|View full text |Cite
|
Sign up to set email alerts
|

Medical system and nutrition improvement for the rural elderly

Abstract: Background Insufficient nutrition intake has negatively influenced the health of the elderly in rural China where the problem of population aging is serious. The present study aims to explore whether the medical system, called the New Rural Cooperative Medical System (NRCMS), can improve the rural elderly’s nutrition intake and the mechanism behind it. Methods The difference in differences (DID) model and the propensity score matchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Medical insurance whatever the public or commercial insurance is helpful to elderly parents to have more energy intake, and this is mainly because medical insurance could reduce the preventative saving and medical cost of elderly parents and then make them have more food expenditure. 35 Knowing the Chinese dietary guideline means the elderly parents owing more health dietary awareness and knowledge, which resulting them in more energy intake. The elderly parents who drink alcohol have a higher energy intake.…”
Section: Baseline Resultsmentioning
confidence: 99%
“…Medical insurance whatever the public or commercial insurance is helpful to elderly parents to have more energy intake, and this is mainly because medical insurance could reduce the preventative saving and medical cost of elderly parents and then make them have more food expenditure. 35 Knowing the Chinese dietary guideline means the elderly parents owing more health dietary awareness and knowledge, which resulting them in more energy intake. The elderly parents who drink alcohol have a higher energy intake.…”
Section: Baseline Resultsmentioning
confidence: 99%
“…Based on data from the China Nutrition and Health Survey(CHNS) and inspired by the link between income uncertainty and nutrient intake, researchers use completely different methods to investigate the effect of the new rural cooperative medical system (NCMS) on rural residents' nutrition intake and draw completely different conclusions (MA et al, 2011;MA & ZHANg, 2011;WANg et al, 2019). Some indicated that NCMS significantly improves the intake of calories, protein and carbohydrate per capita in rural households, but it has no significant effect on fat intake (MA et al, 2011;WANg et al, 2019). Since calories come mainly from carbohydrate and fat in food, grains are the main source of carbohydrates (CHINESE SoCIEty oF NUtRItIoN, 2014), it means that NCMS primarily promotes staple food consumption, and then improves rural residents' calorie intake.…”
Section: Rural Sociologymentioning
confidence: 99%
“…However, in previously relevant studies, both variables are not well controlled and important explanatory variables may be omitted. For example, some studies did not control the intensity and height and weight of the physical activity of migrant workers (MA et al, 2011;MA & ZHANg, 2011); WANg et al (2019) did not control the variables of the height and weight of the elderly in rural areas; MENg et al (2009), LI & CHEN (2017), LI et al (2018) did not control the height and weight of urban residents. the rest of this paper is arranged as follows: Second, putting forward hypotheses through theoretical analysis; third, describing data sources and main statistical methods; Fourth is the results analysis, including the descriptive statistics, the main estimation results, heterogeneity analysis, endogeneity discussion and robustness test; Five is the discussion and conclusion.…”
Section: Rural Sociologymentioning
confidence: 99%